KEANEKARAGAMAN JENIS IKAN DI SUNGAI EMBALOH DESA BANUA UJUNG KECAMATAN EMBALOH HULU KABUPATEN KAPUAS HULU - Ajai, Odilo Noplantino; Anwari, M Sofwan; Dirhamsyah, M (Universitas Tanjungpura, 2020)
The condition of Embaloh River is still well maintained, with clear water and a large variety of fishes. This is because the forest around Embaloh River is still dense; there is no deforestation, mining, and palm oil garden. In such a condition, the river is capable of maintaining a large variety of fishes that have not listed yet. Therefore, this research has the purpose of studying the variety of fishes in Embaloh River, and also to categorize the fishes based on their benefits, whether as decorative fishes, to be eaten, or even as a decorative fish and also to be eaten. The research was conducted on the Embaloh River, Banua Ujung Village, Embaloh Hulu District, Kapuas Hulu Regency. Research Data is obtained by the use of fishing equipment such as mesh, Bubu, Sauk, trawler, burst, and Talom. The method of research using the survey method, the selection of observation stations conducted with (purposive sampling) based on consideration of environmental conditions of the water. This location is made 3 (three) stations on the Embaloh River and 1 (one) station is on the lake (oxbow) called Lake Loane. Lake Loane is a stream of the Embaloh River Moreover, fish of species taken from Embaloh River and Loane Lake, which water from Embaloh River flows to, consist of several families of fish; Cobitidae (1 species), Cyprinidae (13 species), Elopidae (1 species), Grynocheilidae (1 species), Helostomatidae (1 species), Osphronemidae (2 species), Polynemidae (1 species), Pristolepididae (1 species), Sisoridae (1 species), and Syngnathidae (1 species).Keywords: Banua Ujung Village, Embaloh River, Fish Species Diversity, Loane Lake.